The eleven commandments of good teaching : creating classrooms where teachers can teach and students can learn - Gill, Vickie; Gill, Vickie (Thousand Oaks, CA : Corwin Press, 2001)
In this second edition, the author illustrates each commandment with real-life classroom experiences and offers concrete guidance for staying enthusiastic and committed to excellence.
Includes bibliographical references
Keywords: Effective teaching